An emerging view of the diversity, ecology and function of Archaea in alkaline hydrothermal environments. Issue 2 (4th December 2020) - Mueller, Rebecca C; Peach, Jesse T; Skorupa, Dana J; Copié, Valerie; Bothner, Brian; Peyton, Brent M
ABSTRACT: The described diversity within the domain Archaea has recently expanded due to advances in sequencing technologies, but many habitats that likely harbor novel lineages of archaea remain understudied. Knowledge of archaea within natural and engineered hydrothermal systems, such as hot springs and engineered subsurface habitats, has been steadily increasing, but the majority of the work has focused on archaea living in acidic or circumneutral environments. The environmental pressures exerted by the combination of high temperatures and high pH likely select for divergent communities and distinct metabolic pathways from those observed in acidic or circumneutral systems. In this review, we examine what is currently known about the archaea found in thermoalkaline environments, focusing on the detection of novel lineages and knowledge of the ecology, metabolic pathways and functions of these populations and communities. We also discuss the potential of emerging multi–omics approaches, including proteomics and metabolomics, to enhance our understanding of archaea within extreme thermoalkaline systems. Abstract : A synthesis of the distribution, diversity and function of Archaea in high pH, high temperature geothermal systems.